2017
DOI: 10.3892/mmr.2017.8155
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast activation protein-α in tumor cells promotes colorectal cancer angiogenesis via the Akt and ERK signaling pathways

Abstract: Fibroblast activation protein-α (FAP-α) is a cell surface serine protease of the post-prolyl peptidase family, and stromal FAP-α expression may serve important functions in tumor occurrence and progression. In recent years, FAP-α expression in tumor cells has been detected in a number of types of tumor, and its roles in tumor growth and metastasis have been reported. However, the presence of FAP-α in colorectal cancer (CRC) cells lacks sufficient evidence and its role in angiogenesis remains unknown. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Angiogenin secreted by breast tumour cells triggers angiogenic activity in endothelial cells . Vascular remodelling is considered to be one of the key events in metastasis development . MicroRNAs associated with pro‐ and antiangiogenic events include miR‐155, miR‐21, miR‐205 and miR‐let7b .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiogenin secreted by breast tumour cells triggers angiogenic activity in endothelial cells . Vascular remodelling is considered to be one of the key events in metastasis development . MicroRNAs associated with pro‐ and antiangiogenic events include miR‐155, miR‐21, miR‐205 and miR‐let7b .…”
Section: Introductionmentioning
confidence: 99%
“…14 Vascular remodelling is considered to be one of the key events in metastasis development. 15,16 MicroRNAs associated with pro-and antiangiogenic events include miR-155, miR-21, miR-205 and miR-let7b. [17][18][19][20][21][22] Among those, miR-155 is significantly increased in cutaneous melanoma and acts as an oncogene.…”
mentioning
confidence: 99%
“…This study has analyzed the intensity and proportion of FAP expression by immunohistochemical examination. This study suggested that the expression of FAP in the stroma improves tumor prognosis and poor survival in some patients with solid tumor types, including colorectal cancer, but other studies on colorectal cancer did not get statistically significant results, both on the overall survival value, tumor cell invasion, lymph node involvement and distant metastases [26][27][28][29]. Therefore, further exploration is needed to validate the presence of Fibroblast Activation Protein (FAP) in relation to the activity of the stroma in influencing tumorigenesis, angiogenesis, and prognosis, and in the future, it can be used as an adequate treatment in colorectal cancer patients.…”
Section: Introductionmentioning
confidence: 74%
“…The phosphorylation of ERK 1/2 and Smad 2/3, however, was unaffected. Meanwhile, the inhibited phosphorylation of AKT [59,[63][64][65]. Thus, the exact relationships among VEGFA, AKT and p38 in NPC cells merit further exploration.…”
Section: Discussionmentioning
confidence: 99%